173k views
2 votes
Find an explicit solution to the Bernoulli equation. y'-1/3 y = 1/3 xe^xln(x)y^-2

1 Answer

4 votes


y'-\frac13y=\frac13xe^x\ln x\,y^(-2)

Divide both sides by
\frac13y^(-2)(x):


3y^2y'-y^3=xe^x\ln x

Substitute
v(x)=y(x)^3, so that
v'(x)=3y(x)^2y'(x).


v'-v=xe^x\ln x

Multiply both sides by
e^(-x):


e^(-x)v'-e^(-x)v=x\ln x

The left side can be condensed into the derivative of a product.


(e^(-x)v)'=x\ln x

Integrate both sides to get


e^(-x)v=\frac12x^2\ln x-\frac14x^2+C

Solve for
v(x):


v=\frac12x^2e^x\ln x-\frac14x^2e^x+Ce^x

Solve for
y(x):


y^3=\frac12x^2e^x\ln x-\frac14x^2e^x+Ce^x


\implies\boxed{y(x)=\sqrt[3]{\frac14x^2e^x(2\ln x-1)+Ce^x}}

User John Kim
by
6.5k points